Adherence to standard precautions among nursing professionals exposed to biological material - Silmara Elaine Malaguti-Toffano; Silvia Rita Marin da Silva Canini; Renata Karina Reis; Fernanda Maria Vieira Pereira; Adriana Maria da Silva Felix; Patricia Helena Vivan Ribeiro; Elucir Gir (Universidade Federal de Goias, 2015)
This cross-sectional study, developed at a public teaching hospital with 256 nursing professionals, had the aim to: describe occupational exposure events involving potentially infectious biological material among nursing professionals at a teaching hospital and compare the scores of adherence to Standard Precautions (SP). The first stage of data collection was performed using a form with questions regarding the occupational exposure and the psychometric scale "Adherence to SP"; in the second stage, and upon the participants' consent, the medical records of the exposed professionals were analyzed. Adherence to SP was assessed as high and intermediate, according to the answers to the scale items. There was no statistically significant difference between those who had been exposed or not to biological material. The results evidence that only the use of the scale of adherence to SP was not enough to contemplate all factors that may be associated with occupational exposure to biological material.